2007
DOI: 10.2307/30032490
|View full text |Cite
|
Sign up to set email alerts
|

"He Does His Own and Walks Away" Perceptions About Male Attitudes and Practices Regarding Safe Motherhood in Ekiadolor, Southern Nigeria

Abstract: The main study objectives were to highlight male attitudes and practices regarding safe motherhood, and to demonstrate the usefulness of qualitative research methods in studying behaviour-related health problems. The setting was Ekiadolor, a semiurban Nigerian community with an under-resourced district hospital. The study design was a qualitative research, using Focus Group Discussions (FGDs) with females and the local hospital staff as participants, triangulated with Free Listing Interviews (FLIs) and group i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 4 publications
1
29
1
1
Order By: Relevance
“…While this response does not necessarily reflect a high level of male participation, it does imply that married women receive additional support as compared with single respondents. Studies in Edo State [12,13] and Northern Nigeria [14] have however highlighted that male participation in maternal health issues is undesirably low and requires improvement. This highlights an opportunity that exists for improving BPACR and maternal health in rural communities through the education of men on their role in safe motherhood.…”
Section: Discussionmentioning
confidence: 99%
“…While this response does not necessarily reflect a high level of male participation, it does imply that married women receive additional support as compared with single respondents. Studies in Edo State [12,13] and Northern Nigeria [14] have however highlighted that male participation in maternal health issues is undesirably low and requires improvement. This highlights an opportunity that exists for improving BPACR and maternal health in rural communities through the education of men on their role in safe motherhood.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies, Ekiadolor 13 Edo State, Northern Nigeria 6 , El Salvador 2 Central America and Greece 3 equally showed low levels of male involvement during ANC which increased during labour. These studies were purely male studies and data collections were quantitative, except for the Ekiadolor study 13 which was purely a qualitative study and involved female respondents to help cross check the reported findings from male participants.…”
Section: Discussionmentioning
confidence: 99%
“…Aimakhu (1995), a former President of the Society of Gynecology and Obstetrics of Nigeria, linked every maternal death in the country ''to either violence against women by men because she is a female, or a violation or denial of her reproductive rights again by men'' (p. 5). One study conducted in Ekiadolor found that women's perceptions and experiences with maternal health were framed within a context of negative male attitudes and behaviors (Adeleye & Chiwuzie, 2007). The women recounted extramarital affairs, unwillingness of men to allow for family planning methods, men subjecting a pregnant wife to hard work to induce labor, and physical beatings by men (p. 81).…”
Section: National Context: Nigeria and Women's Healthmentioning
confidence: 97%